Gamma-Al2-xMxO3 +/- y (M = Ti4+ through Ga3+): potential pseudo-3D mesoporous materials with tunable acidity and electronic structure - Mathew, Thomas; Sivaranjani, Kumarsrinivasan; Gnanakumar, Edwin S.; Yamada, Yusuke; Kobayashi, Tetsuhiko; Gopinath, Chinnakonda S. (Journal of Materials Chemistry, 2012)
A simple and highly efficient surfactant-free sol-gel process has been developed to obtain nanocrystalline mesoporous gamma-Al2O3 and metal ion incorporated mesoporous gamma-Al2O3 with general formula gamma-Al2-xMxO3 +/- y (where M = Ti4+ through Ga3+). Any one of the first row transition metal (TM) ions along with Ga3+ could be introduced into the gamma-Al2O3 framework in a direct one-pot synthesis process. The generality of the present synthesis recipe for metal ion incorporation in gamma-Al2O3 was demonstrated by preparation of an Al-Ga-M ternary oxide system with the metal ion composition of general formula Al9GaTM (TM = Ti4+ to Zn2+) and their characterization through various physicochemical and spectroscopic techniques. The mesoporous gamma-Al2-xMxO3 +/- y materials showed a BET surface area in the range of 200-400 m(2) g(-1) with a narrow pore size distribution. Wormhole mesoporosity makes the material pseudo-3D (p3D) with a small pore depth of few nm (<10 nm). Metal ions in gamma-Al2O3 lead to changes in the acidity and electronic environment. XRD, TEM, and Al-27 MAS NMR studies demonstrate that the sol-gel process and the disordered mesoporous structure allow Ga and TM ions to be highly distributed and integrated in the gamma-Al2O3 framework. The efficacy of these materials in catalysis has been successfully evaluated for steam reforming of dimethylether: Ni, Cu and Zn containing Al9GaTM oxides showed high activity and stability. The smaller mesochannel depth (<10 nm) and pseudo-3D characteristics that arise due to the wormhole-type disordered mesoporous framework of these alumina materials facilitate mass transport through them without any leaching of metal ions out of the lattice and pore blocking during the reaction, which makes them attractive in catalysis. This preparation method is versatile enough to be used for a reproducible synthesis of metal ion incorporated mesoporous gamma-Al2O3 by varying the metal content and their combinations, and it is expected that many other metal ions could be introduced into the lattice framework for a variety of applications by tuning acidity and electronic structure.